TMEM33 regulates intracellular calcium homeostasis in renal tubular epithelial cells - Malika Arhatte (Nature Portfolio, 2019)
Polycystin-2 (PC2) is an ion channel commonly found mutated in autosomal dominant polycystic kidney disease. Here Arhatte et al. identify transmembrane protein 33 (TMEM33) as a regulator of PC2 function at the endoplasmic reticulum, and find that deletion of TMEM33 protects mice from acute kidney injury.